Efficient pH and dissolved CO2 conditions for indoor and outdoor cultures of green alga Parachlorella - Takagi, Akari; Nagao, Misato; Uejima, Yuya; Sasaki, Daisaku; Asayama, Munehiko (Frontiers in Bioengineering and Biotechnology, 2023)
Efficient pH and dissolved CO2 conditions for indoor (50–450 mL scale) and outdoor (100–500 L scale) culture of a green alga BX1.5 strain that can produce useful intracellular lipids and extracellular polysaccharides were investigated for the first time in Parachlorella sp. The cultures harvested under 26 different conditions were analysed for pH, dissolved CO2 concentration, and the biomass of extracellular polysaccharides. The BX1.5 strain could thrive in a wide range of initial medium pH ranging from 3 to 11 and produced valuable lipids such as C16:0, C18:2, and C18:3 under indoor and outdoor culture conditions when supplied with 2.0% dissolved CO2. Particularly, the acidic BG11 medium effectively increased the biomass of extracellular polysaccharides during short-term outdoor cultivation. The BG11 liquid medium also led to extracellular polysaccharide production, independent of acidity and alkalinity, proportional to the increase in total sugars derived from cells supplied with high CO2 concentrations. These results suggest Parachlorella as a promising strain for indoor and outdoor cultivation to produce valuable materials.